2021
DOI: 10.1093/eurheartj/ehab170
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations of short and long sleep durations with 12 cardiovascular diseases: linear and nonlinear Mendelian randomization analyses in UK Biobank

Abstract: Aims Observational studies have suggested strong associations between sleep duration and many cardiovascular diseases (CVDs), but causal inferences have not been confirmed. We aimed to determine the causal associations between genetically predicted sleep duration and 12 CVDs using both linear and nonlinear Mendelian randomization (MR) designs. Methods and results Genetic variants associated with continuous, short (≤6 h) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 40 publications
11
106
4
Order By: Relevance
“…Previous studies showed that self-reported sleep duration <6 h was a potential pathogenic factor for MI (8). Genetically determined short sleep duration (<6 h) was also a potential causal risk factor of MI (9). Selfreported sleep duration could be calculated as the length of time from bedtime to wake-up time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that self-reported sleep duration <6 h was a potential pathogenic factor for MI (8). Genetically determined short sleep duration (<6 h) was also a potential causal risk factor of MI (9). Selfreported sleep duration could be calculated as the length of time from bedtime to wake-up time.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, some variables related to CVD, such as genetic factors could not be analyzed due to the database limitations. Fifth, mental state and sleep duration were associated with CVD risk [ 36 , 37 ], but we did not analyze the effects of these variables, which may be potentially confounding.…”
Section: Discussionmentioning
confidence: 99%
“…As for lifestyle factors, earlier studies have shown that insufficient sleep is one of the causes of AVS [ 76 ]. A previous MR analysis in the UK biobank about sleep duration and CVD demonstrated that short sleep duration is a potential causal risk factor for several CVDs [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for lifestyle factors, earlier studies have shown that insufficient sleep is one of the causes of AVS [ 76 ]. A previous MR analysis in the UK biobank about sleep duration and CVD demonstrated that short sleep duration is a potential causal risk factor for several CVDs [ 76 ]. Poor sleep quality may affect CVD through pathways, including inflammation, nervous system dysfunction, and metabolic abnormalities [ 77 , 78 , 79 ], indicating that improving sleep quality may prevent CVD development.…”
Section: Discussionmentioning
confidence: 99%